An Analysis of YouTube Tourism Video in Teaching Students' Speaking Skill - Nabila Lubna Faiza; Iin Rachmawati (Penerbit STKIP PGRI Bangkalan, 2023)
Currently, rapidly developing technology has been used in education. YouTube is one of the technologies that can be used as an effective learning media in speaking skills of each student, especially speaking. This study aims to describe the implementation and the students’ responses toward the use of YouTube tourism video in teaching students’ speaking skill. The method in this study used qualitative research which focus on case study research. It involved the eleventh-grade students of SMAN 3 Bangkalan as the subject of the research. The data were obtained through the observation during the teaching and learning process and an interview with the students. In this study, the researcher accomplished several steps to analyse the data, namely organizing and familiarizing, coding and reducing, interpreting and representing. The first research findings reveal that YouTube Tourism videos are used by teachers and students inside and outside the classroom. Teachers take advantage of YouTube tourism to provide writing assignments, speaking assignments and feedback on students' speaking. Meanwhile, students use YouTube to provide corrections and suggestions to their friends. The second finding revealed that students gave positive responses on the use of YouTube Tourism in speaking. The students say that YouTube is media that is easy to use, effective, and attractive. It also develops students writing and speaking skills are able to motivate students in speaking.